Pengaruh pemberian susu almond terhadap glukosa darah puasa pada tikus diabetes - Ningsih, Ryta Ristantia; Probosari, Enny; Panunggal, Binar (Jurnal Gizi Indonesia (The Indonesian Journal of Nutrition), 2019)
Background: Type 2 Diabetes Mellitus is a group of metabolic diseases with characteristic hyperglycemia that occurs due to abnormalities in insulin secretion and insulin action. Diet plus high fiber can help control glucose levels. Almond contains fiber, vitamin E, and magnesium that contributes to the fasting blood glucose levels. This study aimed to analyze the effect of almond milk to the fasting blood glucose diabetic rats.Method: This study used an experimental design with pre-post test control group design. The sample were Rattus norvegicus Wistar which were divided into 4 groups: K (-), K (+), A1 and A2. Almond milk was given in the group treatmeant for 14 days with a dose of 4.32 ml and 8.64 ml. Fasting blood glucose measurement taken before and after treatment used Oxidase Glucose - Peroxidase Aminoantypirin (GOD PAP). Analysis of data used paired t-test, ANOVA and Post Hoc.Results: The fasting blood glucose levels decreased significantly (p = 0.01) in the treatment group which were intervened with almond milk. A decrease in fasting blood glucose levels in a dose treatment group 1 for 116.96 ± 4.45 (p = 0:01), whereas in the group treated at a dose of 2 for 155.53 ± 3.15 (p = 0.01). There were a significant difference in decreased of the fasting blood glucose levels between the two treatment groups (p = 0.01).Conclusion: Giving a dose almond milk 4.32 ml and 8.64 ml for 14 days can lower the fasting blood glucose levels significantly.